TEACHER-CENTERED LEARNING AND STUDENT-CENTERED LEARNING APPROACHES IN NURSING SCHOOL: WHICH ONE IS BETTER? - Intansari Nurjannah; Fatihatul Husniyah; Totok Harjanto (Belitung Nursing Journal, 2017)
Background: Student academic achievement is influenced by learning instruments such as: teaching staff, facility and infrastructure as well as the curricular component. Teacher-Centered Learning (TCL) or Student-Centered Learning (SCL) will also contributes to student’s outcomes as an approach to apply a curricular component. Objective: To compare students’ academic achievement levels between undergraduate students who follow TCL and SCL approaches in nursing school. Methods: This was a quantitative research with a descriptive analytic method comparative study. The entire undergraduate student population in one of nursing school in Indonesia from 1999 to 2011 was included in this research. The relevant data in this study was GPA score and length of study. A total sampling method was performed to select 918 subjects involved in the study. The data were analyzed using Mann-Whitney test. Results: Academic achievement was assessed from GPA score and length of study. The average GPA of students who followed a TCL approach was 3.28, while the score for those who followed a SCL approach was 3.54 with p-value of 0.00. The average length of study of students who followed a TCL approach was 4 years 3 months; while those with a SCL approach was 4 years 1 month with p-value of 0.279. Conclusions: There was a significant difference on GPA score and no significant differences on the length of study between the undergraduate students who followed a TCL versus a SCL approaches.